2007
DOI: 10.1021/ja075373f
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Protease Stability of Peptides Containing Fluorinated Amino Acids

Abstract: Selective fluorination of peptides results in increased chemical and thermal stability with simultaneously enhanced hydrophobicity. We demonstrate here that fluorinated derivatives of two host defense antimicrobial peptides, buforin and magainin, display moderately better protease stability while retaining, or exhibiting significantly increased bacteriostatic activity. Four fluorinated analogues in the buforin and two in the magainin series were prepared and analyzed for (1) their ability to resist hydrolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
189
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(194 citation statements)
references
References 54 publications
4
189
1
Order By: Relevance
“…Selective fluorination of peptides enhanced chemical and thermal stability with increased hydrophobicity Meng et al demonstrated that fluorinated derivatives of two AMPs, buforin and magainin, show similar or enhanced antibacterial activity and improved protease stability (Meng and Kumar, 2007). It is interesting that hemolytic activity of peptides in the buforin series was negligible while fluorinated magainin analogues displayed increased hemolysis compared to the parent peptides.…”
Section: All D-form Of Aamps Increase Antimicrobial Activity and Stabmentioning
confidence: 99%
“…Selective fluorination of peptides enhanced chemical and thermal stability with increased hydrophobicity Meng et al demonstrated that fluorinated derivatives of two AMPs, buforin and magainin, show similar or enhanced antibacterial activity and improved protease stability (Meng and Kumar, 2007). It is interesting that hemolytic activity of peptides in the buforin series was negligible while fluorinated magainin analogues displayed increased hemolysis compared to the parent peptides.…”
Section: All D-form Of Aamps Increase Antimicrobial Activity and Stabmentioning
confidence: 99%
“…Upon binding to membranes, they often organize as α-helices with hydrophobic and hydrophilic residues on opposite faces, a feature referred to as secondary amphipathic character. Designers of synthetic CAPs found that it was possible to modify CAP activity towards microbial and mammalian cells independently by varying the hydrophobicity, as well as the number and the position of the positive charges in the amphiphilic structure [3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Melittin-21Q exhibited a reduced or similar binding to DMPC and to DMPG bilayers compared to native melittin, suggesting a favorable or a limited contribution of the cationic C-terminal portion to membrane affinity. Another investigation, using tryptophan fluorescence, revealed that melittin and its Cterminal truncated versions , and [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], all showed an increased affinity for 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC)/1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1'-rac-glycerol) (POPG) 70/30 large unilamellar vesicles (LUVs) compared POPC LUVs 47 (See Supporting Information). These findings highlighted the role of attractive electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…21 The introduction of three hFLeu residues stabilizes the folding of a 4 F 3 d by -8.6 kcal mol À1 relative to a 4 H. For the present studies we initially synthesized three new a 4 variants: a 4 F 3 (6-13), which contains hFLeu in place of Leu at positions 6, 10, and 13; a 4 F 3 (17)(18)(19)(20)(21)(22)(23)(24), which contains hFLeu in place of Leu at positions 17, 20, and 24; and a 4 tbA 6 , which contains the leucine analog b-t-butylalanine in place of Leu at all 6 ''a'' and ''d'' positions.…”
Section: Effect Of Hfleu and Tbala On Stability Of A 4 Proteinsmentioning
confidence: 99%
“…12,[15][16][17][18][19][20][21][22][23] In most cases, these modified proteins display significantly increased stability toward unfolding by chemical denaturants and organic solvents, as well as increased resistance to proteolytic degradation. 20,[24][25][26] Currently, our understanding of how fluorination stabilizes protein folding is impeded by the lack of structures for proteins containing highly fluorinated amino acids. Gellman and coworkers recently determined both NMR and X-ray structures of chicken villin headpiece subdomain (cVHP) in which pentafluorophenylalanine (pFPhe) replaced one of three Phe residues in the core.…”
Section: Introductionmentioning
confidence: 99%